Satellite Tracking Reveals Nesting Patterns, Site Fidelity, and Potential Impacts of Warming on Major Green Turtle Rookeries in the Red Sea - Shimada, Takahiro; Duarte, Carlos M.; Al-Suwailem, Abdulaziz M.; Tanabe, Lyndsey K.; Meekan, Mark G. (Frontiers in Marine Science, 2021)
Major aggregations of nesting green turtles (Chelonia mydas) occur in the northern Red Sea, although little is known about the reproductive ecology of this endangered species in the region. To address this issue, we satellite-tracked 30 female green turtles to document their movements and to identify factors driving habitat use at two major rookeries in the Red Sea, Jazirat Mashabah (Mashabah Island) and Ras Al Baridi in Saudi Arabia. Between successive nesting events, turtles displayed high fidelity to nesting beaches and adjacent in-water habitats (inter-nesting habitats). Using generalized linear mixed models, we estimated the mean probability of nesting per beach emergence (nesting success rate) to be 0.628, and the mean duration between a successful nesting event and the successive emergence onto the beach (re-nesting interval) to be 10.8 days at each site. The nesting success rate was relatively high (>0.8) when the preceding daytime land surface temperature (LST) was lower than 37°C but decreased with elevated daytime LST (<0.4 when >47°C). Re-nesting interval was longer at lower water temperatures and towards the end of the nesting season of individuals. Our study improves the robustness of abundance estimates from census data (e.g., track counts) and shows that the protection of nesting and inter-nesting habitats during a breeding season would be an effective conservation strategy for the species. We discuss how global warming could increase energy expenditure due to lowered nesting success, ultimately compromising the reproductive fitness of these populations.